A Quali-Quantitative Analysis of Food Advertising in Italian Chilldren’s National TV Programming: Implications for School-Based Nutrition Educational Programs - Pellai, Alberto; Nobile, Marta; Luti, Cristina (Journal of Nutritional Therapeutics, 2012)
Globally it has been estimated that 10% of children and teens aged 6 to 18 are overweight or obese. Media and advertising agencies are considered social organizations capable to playing a central role in both promoting and challenging childhood obesity. To have a better understanding of this problem, it was investigated the quantity and the typology of advertising on air during children’s television broadcastings in Italy over a period of three months, analyzing all the TV programming targeting children aired in the six main TV national channels. This paper focuses on the main results which were obtained and suggests to integrate traditional nutritional educational programs targeting children with components taken from the field of media education.